2022
DOI: 10.1186/s13014-022-02006-5
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy interruption due to holidays adversely affects the survival of patients with nasopharyngeal carcinoma: a joint analysis based on large-scale retrospective data and clinical trials

Abstract: Background The impact of radiotherapy interruption due to the Spring Festival holidays in China on the survival of patients with nasopharyngeal carcinoma (NPC) is unclear. Methods Nontrial patients with locoregionally advanced NPC receiving radiotherapy plus induction chemotherapy (IC) and/or concurrent chemotherapy (CC) were included (N = 5035) and divided into two groups based on the Spring Festival-induced radiotherapy interruption. Kaplan–Meier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Nasopharyngeal carcinoma, as a malignant tumor originating from the epithelium of the nasopharyngeal mucosa, mostly presents in the hanging wall and sidewall of the nasopharynx. Its incidence is 30/100,000–50/100,000, and it is most prevalent among the yellow race [ 1 , 2 ]. Therefore, deeper research on this disease can reduce the medical burden in China.…”
Section: Introductionmentioning
confidence: 99%
“…Nasopharyngeal carcinoma, as a malignant tumor originating from the epithelium of the nasopharyngeal mucosa, mostly presents in the hanging wall and sidewall of the nasopharynx. Its incidence is 30/100,000–50/100,000, and it is most prevalent among the yellow race [ 1 , 2 ]. Therefore, deeper research on this disease can reduce the medical burden in China.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the 3-year OS outcome in our study was superior to that reported in the Intergroup Study 0099 16 and other studies 46,49 , which applied a dual approach of CCRT combined with AC. Studies have reported that IC increases the waiting time for radiotherapy and interrupts the radiation treatment, resulting in accelerated tumor growth and reduced treatment e cacy [50][51][52][53] . However, another reason may be that our IC group has increased the interrupts the radiation and the low completion rate of 3-cycle CC for radiotherapy due to the lack of PFS and other outcomes bene ts.…”
Section: Discussionmentioning
confidence: 99%
“…In order to achieve better prognosis, an uninterrupted routine radiotherapy schedule is an essential necessity for precise radiotherapy of nasopharyngeal carcinoma ( 36 ). Disruptions in radiotherapy, however, are inevitable for several unavoidable factors, such as public holidays ( 37 ) (the largest share, about 39-46%), machine failures, patient compliance, and adverse effects of treatment ( 38 ). Similarly, because of the pandemic of Corona Virus Disease 2019, confirmed positive patients had longer treatment interruptions, which led to fewer patients completing radiotherapy, thus increasing local disease progression ( 39 ).…”
Section: Interruption Of Radiotherapymentioning
confidence: 99%